Navigating nutritional information while living with metastatic cancer: a qualitative study of patient experiences and needs - Barbara S van der Meij; Manon GA van den Berg; Iris EC Nagtegaal; Floortje K Ploos van Amstel; Petronella B Ottevanger; Anja JThCM de Kruif (Supportive Care in Cancer, 2026)
Abstract Purpose Nutrition often becomes a prominent concern for patients living with metastatic cancer. While patients frequently seek nutritional information to support their health and manage treatment-related challenges, they may encounter inconsistent advice from different sources. This study aimed to explore how patients with metastatic cancer perceive and navigate nutritional information, and to identify their experiences and needs regarding nutritional support during systemic therapy. Methods A qualitative study using semi-structured interviews was conducted among patients with metastatic cancer receiving systemic therapy. Interviews were audio-recorded, transcribed verbatim and analyzed using reflexive thematic analysis. Results Twenty-four patients (median age 55 y; 15 men; 9 women) with various tumor types participated. Three overarching themes were identified. First, nutrition became a more prominent concern after diagnosis, with patients reflecting on the role of nutrition during and after cancer treatment while adapting to treatment-related eating difficulties. Second, patients actively navigated nutrition-related information and advice from multiple sources, often encountering uncertainty and conflicting messages. Third, patients expressed a need for personalized, trustworthy and coordinated nutritional support. Respondents valued practical guidance tailored to their individual circumstances and preferred greater consistency between healthcare professionals. Conclusion For many patients with metastatic cancer the challenge is not only obtaining nutritional information but also navigating and applying information from multiple sources in daily life. Nutritional support should therefore extend beyond information provision alone and include personalized, coordinated guidance that helps patients make informed decisions and manage nutritional concerns throughout treatment.